Peningkatan hasil penilaian matematika tentang bentuk bangun datar penggunaan permainan puzzel dengan menerapkan model pembelajaran contextual teaching and learning pada peserta didik kelas I sekolah dasar - Sumartini, Sumartini (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This study aims to improve the results of the Knowledge Assessment of Class I Students at SD Negeri 3 Jangkungharjo, Brati District, Grobogan Regency Semester 1 Academic Year 2022/2023. The type of research used is Classroom Action Research which consists of 2 cycles. The research subjects were Class I students of SD Negeri 3 Jangkungharjo, totaling 26 students (12 boys and 14 girls). Data analysis used quantitative descriptive analysis techniques with the highest, lowest and average values presented in tabular form and then described based on the data that had been analyzed and conclusions drawn. The results of the study show an increase in the results of the Student Knowledge Assessment in the process of learning mathematics. The class average in the Pre-Cycle was 63.07. After the action in Cycle I, the average was 76.56. In other words, there was an increase of 13.49. Then the Cycle II action was carried out again with a class average of 85.76. The increase in the average value from Cycle I to Cycle II was 9.2. The completeness of the results of the Student Knowledge Assessment also increased from the Pre-Cycle, Cycle I and Cycle II. Overall Class II students are 26 students. In the Pre-Cycle, 14 students (53.85%) had completed because their grades were above the KKM, the remaining 12 students (46.15%) did not complete because their grades were still below the KKM. In Cycle I, 21 students (80.77%) had completed it, while 5 students (19.23%) did not complete it. After the action was carried out in Cycle II, as many as 26 students scored above the KKM or completeness reached 100%. Thus, the implementation of Cycle II actions was declared successful. The conclusion of this study is that puzzle games can improve the Knowledge Assessment Results of Grade I Students at SD Negeri 3 Jangkungharjo, Brati District, Semester 1 Academic Year 2022/2023. Suggestions from researchers are to improve the results of the Knowledge Assessment of Learners on Flat Shape Materials by using a puzzle game by applying the Contextual Teaching and Learning Learning Model.